2012
DOI: 10.1038/sc.2012.111
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of spinal cord perfusion by using contrast-enhanced ultrasound in a porcine model with acute spinal cord contusion

Abstract: Objectives: To quantify spinal cord perfusion by using contrast-enhanced ultrasound (CEUS) in a porcine model with acute spinal cord injury. Methods: Microcirculatory changes of acute spinal cord injury were shown by CEUS in a porcine model with spinal cord contusion at three selected time points, coupling with conventional ultrasound (US) and Color Doppler US (CDFI). Time-intensity curves and perfusion parameters were also obtained by autotracking contrast quantification (ACQ) software in the epicenter of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…1 Various studies in clinical and experimental settings have shown that ultrasound (US) imaging can be used to visualize the PH subsequent to SCI. [15][16][17][18][19][20][21] In experimental studies, the highest frequencies used were 10-12 MHz, [18][19][20][21] but the small diameter of the rat spinal cord (3-4 mm) limited the resolution of imaging. More recent US devices using very high frequencies (40-55 MHz) have been specifically designed to image small animals with spatial resolutions as low as 30 microns per pixel.…”
Section: Introductionmentioning
confidence: 99%
“…1 Various studies in clinical and experimental settings have shown that ultrasound (US) imaging can be used to visualize the PH subsequent to SCI. [15][16][17][18][19][20][21] In experimental studies, the highest frequencies used were 10-12 MHz, [18][19][20][21] but the small diameter of the rat spinal cord (3-4 mm) limited the resolution of imaging. More recent US devices using very high frequencies (40-55 MHz) have been specifically designed to image small animals with spatial resolutions as low as 30 microns per pixel.…”
Section: Introductionmentioning
confidence: 99%
“…Huang and colleagues used the modified Tarlov score, which is a shorter, 4-point scale with 0 representing no locomotion and 4 indicating normal gait. 52 , 53 …”
Section: Discussionmentioning
confidence: 99%
“…Hematoxylin and eosin (H&E) is the most common stain and can depict general morphology and the degree of tissue damage. 27 , 33 , 34 , 43 , 53 , 54 Eriochrome cyanine R, commonly used in conjunction with the counterstain cresyl violet or Neutral Red, can help delineate and measure areas of white and gray matter, allowing for analysis of lesion size and neuronal degeneration. 11 , 25 , 37 , 38 , 42 , 45 , 47 , 48 , 55–57 Luxol fast blue can also be used with cresyl violet counterstain to identify myelinated fibers in white matter and the residual preserved tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…dexterity and locomotion), the similarities in anatomy of the vertebral column and spinal cord represent a good compromise ( Lee et al, 2013 ; Schomberg et al, 2017 ). This explains the increased number of pig studies over the past decades ( Benavides et al, 2017 ; Bernards and Akers, 2006 ; Hachmann et al, 2013 ; Hong et al, 2016 ; Huang et al, 2013 ; Jones et al, 2012 , 2013 ; Kowalski et al, 2016 ; Kuluz et al, 2010 ; Kwon et al, 2015 ; Lee et al, 2013 ; Martirosyan et al, 2015 ; Navarro et al, 2012 ; Okon et al, 2013 ; Santamaria et al, 2018 ; Streijger et al, 2015 , 2016 , 2017 ; Tigchelaar et al, 2017 ; Zahra et al, 2010 ; Zurita et al, 2008 , 2012 ). Despite this growing interest in the pig model, utilizing it requires a specific infrastructure, a substantial budget and several types of expertise that can be challenging to gather.…”
Section: Introductionmentioning
confidence: 99%